Neurophysiological responses of globus pallidus internus during the auditory oddball task in Parkinson's disease - Alanazi, Frhan I.; Al-Ozzi, Tameem M.; Kalia, Suneil K.; Hodaie, Mojgan; Lozano, Andres M.; Cohn, Melanie; Hutchison, William D. (Neurobiology of disease, 2021)
Parkinson's disease can be associated with significant cognitive impairment that may lead to dementia. Deep brain stimulation (DBS) of the subthalamic nucleus is an effective therapy for motor symptoms but is associated with cognitive decline. DBS of globus pallidus internus (GPi) poses less risk of cognitive decline so may be the preferred target. A research priority is to identify biomarkers of cognitive decline in this population, but efforts are hampered by a lack of understanding of the role of the different basal ganglia nuclei, such as the globus pallidus, in cognitive processing. During deep brain stimulation (DBS) surgery, we monitored single units, beta oscillatory LFP activity as well as event related potentials (ERPs) from the globus pallidus internus (GPi) of 16 Parkinson's disease patients, while they performed an auditory attention task. We used an auditory oddball task, during which one standard tone is presented at regular intervals and a second deviant tone is presented with a low probability that the subject is requested to count and report at the end of the task. All forms of neuronal activity studied were selective modulated by the attended tones. Of 62 neurons studied, the majority (51 or 82%) responded selectively to the deviant tone. Beta oscillatory activity showed an overall desynchronization during both types of attended tones interspersed by bursts of beta activity giving rise to peaks at a latency of around 200 ms after tone onset. cognitive ERPs recorded in GPi were selective to the attended tone and the right-side cERP was larger than the left side. The averages of trials showing a difference in beta oscillatory activity between deviant and standard also had a significant difference in cERP amplitude. In one block of trials, the random occurrence of 3 deviant tones in short succession silenced the activity of the GPi neuron being recorded. Trial blocks where a clear difference in LFP beta was seen were twice as likely to yield a correct tone count (25 vs 11). The data demonstrate strong modulation of GPi neuronal activity during the auditory oddball task. Overall, this study demonstrates an involvement of GPi in processing of non-motor cognitive tasks such as working memory and attention, and suggests that direct effects of DBS in non-motor GPi may contribute to cognitive changes observed post-operatively. •Parkinsonian GPi neurons respond selectively to deviant tones of the oddball task.•Beta LFPs recorded from GPi are modulated during attending to the tones.•Cognitive ERPs amplitude was larger in the trials with significant beta modulation.•Basal ganglia networks are involved in the circuits that process cognitive tasks.•Effect of DBS in GPi may contribute to the cognitive decline seen postoperatively.